The gendered impact of NAADS on rural households : a case study o f Aputi sub-county, Amolatar district, Northern Uganda - Akullo, Patrick Roy. (Kampala, 2015)
Unpublished dissertation (M.A. Gender studies) - Makerere University , 2015
Includes bibliographical references (p. 56-61).
Keywords: Rural women -- Uganda; Agricultural extention work -- Uganda